개화형상을 모사한 가항력 돛 수납최적화 - 김병규(Byungkyu Kim); 김희경(Heekyung Kim); 정진원(Jinwon Jung); 이건희(Gunhee Lee); 이동윤(Dongyun Lee); 최준우(Junwoo Choi) (항공우주시스템공학회지, 2017)
In this paper, we propose a new folding method (the blossom method) to increase storage efficiency of drag-sail. To resolve the issue caused by increase in the thickness of the sail, we allowed margin space (offset) along the folding line and made holes at the intersection of offset lines to prevent distortion of film. In addition, to verify applicability of the blossom method, we fabricated quarter of the sail by using Mylar film and conducted a deployment experiment. If the blossom method is applied, storage ratio (storage volume: deployed area) is 1: 68.64, that is approximately 1.88 times more than the z-fold method of folding sailing. 본 논문에서는 drag-sail의 수납 효율을 높이기 위해 새로운 접기 방법인 blossom method를 제안하였다. 가항력 돛을 접을수록 두께가 늘어남에 따라 발생하는 문제점을 해결하기 위해 접히는 라인에 여유 공간(offset)을 주고, offset film 라인이 교차하는 지점에는 구멍을 뚫어 film의 일그러짐을 방지하였다. 또한, blossom method의 적용 가능성을 확인하기 위해 mylar film으로 제작하여 전개 실험을 수행하였다. Blossom method를 적용할 경우, 수납부피 대비 전개면적 비인 수납비는 1: 68.64로 기존의 가항력 돛 접기 방법인 z-fold method보다 약 1.88배 향상되었으며, 전개 실험 결과 구멍이나 jamming에 의한 손상이 없는 것을 확인하였다.